2016
DOI: 10.5336/healthsci.2015-48237
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Dietary Applications in Hypertensive Patients and Eating Disorders

Abstract: A AB BS ST TR RA AC CT T OOb bj je ec ct ti iv ve e: : Many studies on prevention and treatment of hypertension show that some special nutrition and diets are effective on blood pressure. The aim of this study is to investigate whether the dietary applications in hypertension patients are correlated with eating disorders or not. M Ma at te er ri ia al l a an nd d M Me et th h--o od ds s: : The study was conduced in eight different centers among Family Health Centers in Sakarya. The test group consisted of 86 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…In our previous study, we investigated whether the dietary appilcations in hypertensive patients were correlated with eating disorders or not. 30 We found that, compared to normal subjects, patients with hypertension exhibited higher EAT and BITE scores. In this study, 19.7% of diabetic patients and 24.4% of hypertensive patients had eating disorders, which is an important finding that requires further research.…”
Section: Discussionmentioning
confidence: 62%
“…In our previous study, we investigated whether the dietary appilcations in hypertensive patients were correlated with eating disorders or not. 30 We found that, compared to normal subjects, patients with hypertension exhibited higher EAT and BITE scores. In this study, 19.7% of diabetic patients and 24.4% of hypertensive patients had eating disorders, which is an important finding that requires further research.…”
Section: Discussionmentioning
confidence: 62%
“…Öte yandan klinik olmayan gruplarda bu ölçeğin faktör yapısının çeşitli çalışmalarda farklılaştığı da rapor edilmiştir (Koslowsky ve ark., 1992; Rogoza, Brytek-Matera ve Garner, 2016). Bu form ülkemizde de bazı çalışmalarda kullanılmış olmasına karşın (örn., Çam, 2017;Durat, Erol, Çevirme, Kaynak ve Yıldız 2016;Gümüş, 2014;Koçak, 2009) ölçeğin psikometrik özellikleri henüz detaylı olarak araştırılmamıştır. Ölçeğin 40 soruluk formunun kısaltılarak kullanıldığı araştırmalarda, yalnızca araştırmada kullanımı için çeviri işlemi yapıldığı (Bayraktar, 2015), bazen sadece YTT-40'dan soruların seçilerek alındığı (Çam, 2017;Durat ve ark., 2016;Gümüş, 2014) gözlenmekte, sıklıkla da ölçeğin kısa formuna dair geçerlik-güvenirlik özelliklerinin rapor edilmediği görülmektedir.…”
Section: Yeme Tutum Ve Davranışlarıunclassified